Intra-abdominal Mixed Germ Cell Tumor (Seminoma and Choriocarcinoma) in an Adult with Cryptorchidism: A Rare Case Report and Surgical Approach - Proginova Dian Yudatama; Syaeful Agung Wibodo (Open Access Indonesian Journal of Medical Reviews, 2025)
Intra-abdominal testicular germ cell tumors (TGCTs) arising from cryptorchid testes represent a rare but clinically significant entity in adult urology. Cryptorchidism, or undescended testis (UDT), persists as the most prominent risk factor for testicular malignancy, and its delayed diagnosis, particularly when testes reside intra-abdominally, frequently leads to complex presentations often discovered at an advanced stage. This report details the case of a young adult male diagnosed with a voluminous intra-abdominal mixed germ cell tumor, incorporating both seminoma and highly aggressive choriocarcinoma components, originating from a previously unrecognized undescended testis, highlighting the multifaceted challenges in diagnosis and management. A 29-year-old Indonesian male presented with a constellation of symptoms including persistent abdominal pain, progressive bloating, and patient-acknowledged abdominal mass. Pertinent clinical findings included bilaterally non-palpable testes within the scrotum and a large, firm, tender intra-abdominal mass upon examination. Contrast-enhanced computed tomography (CT) delineated a massive abdominopelvic tumor consistent with a primary testicular neoplasm, critically associated with significant para-aortic lymphadenopathy and confirming bilateral intra-abdominal undescended testes. Serological investigation revealed a markedly elevated alpha-fetoprotein (AFP) level (>400.00 ng/mL), strongly suggesting a non-seminomatous component. Consequently, the patient underwent an exploratory laparotomy, which confirmed the CT findings and revealed the tumor originating from the left intra-abdominal testis. A comprehensive surgical resection involving bilateral radical orchiectomy was performed, yielding a specimen measuring 20x15x15 cm and weighing 2.865 kg. Subsequent histopathological examination definitively classified the tumor as a mixed germ cell tumor with distinct seminoma and choriocarcinoma elements arising from the left testis; the contralateral right testis exhibited only atrophic changes consistent with UDT. In conclusion, the confluence of adult presentation, bilateral cryptorchidism, intra-abdominal location, massive tumor burden, and aggressive mixed histology (seminoma/choriocarcinoma) exemplifies the complexities encountered in managing such rare TGCT cases. Surgical extirpation via laparotomy remains indispensable for bulky intra-abdominal disease, providing both diagnostic confirmation and cytoreduction. Optimal patient outcomes mandate a meticulously planned, multidisciplinary approach integrating surgery with risk-stratified systemic chemotherapy, guided by precise histopathological analysis and serial tumor marker assessment.